TRANSPLANTASI TERUMBU KARANG UNTUK PERBAIKAN HABITAT DAN KEBERLANJUTAN SUMBER DAYA IKAN DI PERAIRAN TELUK SALEH - Kautsari, Neri; Hidayat, Petira Rimba; Ramadhan, Naufal Gumilang; Solihin, M (Universitas Mataram, 2024)
Coral reefs ecosystem degradation in Saleh Bay results from human impacts such as coral quarrying, dredging, dynamite fishing, tourist damage and run-off of sediment, ship groundings, fertilizer and pesticides as a result of changing land-use. The aim of this project is to improve coral reef ecosystems through coral transplantation. The primary objectives of coral transplantation are to improve reef `quality' in terms of live coral cover, biodiversity and topographic complexity. This coral reef transplantation project was carried out in the waters of Saleh Bay. This project was carried out from June to July 2024. The stakeholders involved were universities, village governments, NGOs (Yayasan Bentang Alam Nusantara) and the Labuhan Kuris Village community. The FGD method was used to collect information from stakeholders and determine the role of each stakeholder. Coral reef transplantation uses table-shaped iron media. The coral species planted are acropora sp. Coral transplants are placed in the waters of Saleh Bay. The result of this activity is that there are two coral reef transplant units. The type planted is Acropora sp. The success of this activity is due to the collaboration between community groups, government and NGOs. Based on the evaluation results during the activity, it can be concluded that the coral reef transplantation in this activity was successfully carried out with the indicator of the planting of two coral transplant units using a rectangular iron frame media (table). The success of this activity was due to collaboration between stakeholders.